Gestión operativa de la estación experimental tropical Pichilingue - INIAP y su impacto en el sector agrícola del cantón Mocache, período 2021-2022 - Tubay Gorozabel, Darling Rafael (2023)
The operational management of the Pichilingue Tropical Experimental Station has had a positive impact on the agricultural sector of the Mocache canton during the study period. Through the implementation of innovative practices, it has contributed to the quality of crops, as well as the transfer of knowledge to local farmers. The present study focuses on the Pichilingue Tropical Experimental Station – INIAP which is located at km 5 of the Quevedo-El Empalme road, Province of Los Ríos. The objective of this study was to evaluate the impact of the operational management of the Pichilingue Tropical Experimental Station - INIAP on the agricultural sector of the Mocache canton, period 2021-2022. In this research project, a mixed methodology was used with a qualitative and quantitative approach divided into three phases: First phase, the offices and departments were visited, second, an interview was carried out with the Director and operational technicians of the INIAP and finally, surveys were carried out. to 365 agricultural producers that was obtained from the sample of the current population of the Mocache canton divided into five family members. It was determined that the impact of activities developed by the EETP-INIAP is considered to have had a positive impact on cocoa pruning. Agricultural producers are 51.78% satisfied with the support they have been given, improving productivity, which It is recommended that better planning continue to be implemented with the purpose of continuing to improve the quality of life of the farmers of the Mocache canton.